TEKANAN UDARA DALAM PERSPEKTIF SAINS DAN AL-QUR’AN - Nuraini Fatmi (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2020)
The objectives of this study are: 1. To see the function of air pressure from a scientific perspective. 2. To see the function of air pressure in the perspective of the Qur'an. 3. To see the relationship between the study of the function of air pressure from a scientific perspective and the Koran. This study used qualitative research methods. The type of research used in this research is library research. The instrument in qualitative research is a person or human instrument, namely the researcher himself. As a human instrument in this study, researchers must have broad insight and theory in order to be able to ask, analyze, take pictures and construct the social conditions under study to be clearer and show. The technique of reading data that researchers use in library research is by reading, interviewing and triangulation. Research results: 1. Study of Air Pressure Function in Science Perspective is according to science air pressure is a force that moves air particles carrying air particles in the direction of the earth's force. 2. The study of the function of air pressure in the perspective of the Koran is based on the perspective of the Koran, the air pressure is described into the atmospheric layer which is described in QS: Al-An'am (6) verse 125. 3. The relationship between the study of the pressure function The air in the perspective of science and the Koran is the relationship between science and the Qur'an expressed as an integrated relationship. This integration can be described in two forms, namely natural theology (natural theology) which views scientific findings as a means of reaching God, and natural theology (theology of nature).